2018
DOI: 10.1097/ruq.0000000000000375
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Analysis of Contrast-enhanced Ultrasonography Effectiveness in Reducing Time to Diagnosis and Imaging-related Expenditures at a Single Large United States County Hospital

Abstract: Hepatic and renal lesions detected during ultrasound examinations frequently require subsequent contrast-enhanced computed tomography (CT) or magnetic resonance imaging (MRI) for characterization, delaying time to imaging diagnosis and increasing overall health care expenditures. Contrast-enhanced ultrasonography (CEUS) is a comparatively low-cost diagnostic tool that is underutilized in the evaluation of such indeterminate or suspicious hepatic and renal lesions. A retrospective chart review of CEUS examinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 11 publications
1
24
0
Order By: Relevance
“…This is significantly less than the cost of contrast CT or MRI. The cost‐effectiveness of healthcare is always of high priority in the public system and CEUS has certainly proven to be cost‐effective in a range of applications and clinical settings 8‐10 . The favourable balance of cost, safety and utility of CEUS is already being recognised by health authorities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is significantly less than the cost of contrast CT or MRI. The cost‐effectiveness of healthcare is always of high priority in the public system and CEUS has certainly proven to be cost‐effective in a range of applications and clinical settings 8‐10 . The favourable balance of cost, safety and utility of CEUS is already being recognised by health authorities.…”
Section: Discussionmentioning
confidence: 99%
“…CEUS has an excellent safety profile, 5 specifically when compared with contrast CT which requires the use of ionising radiation 6 and nephrotoxic contrast agents 7 . CEUS is also more cost‐effective than CT and MRI 8‐10 …”
Section: Introductionmentioning
confidence: 99%
“…More recently, excellent results have been demonstrated using contrast-enhanced US (CEUS)[ 30 ]. Main advantages of CEUS over contrast-enhanced CT scan and MRI are lack of radiation exposure, avoidance of contrast-induced nephropathy (CIN) or nephrogenic systemic sclerosis, and cost savings[ 31 ]. In order to avoid diagnostic delays that may compromise the chance of conservative treatment or unnecessary interventions that may irreversibly damage the transplanted kidney, an allograft biopsy should be obtained whenever possible[ 7 , 14 , 18 ].…”
Section: Diagnosismentioning
confidence: 99%
“…Therefore, CEUS is a good modality to confirm subtle enhancement when it cannot be seen on CT/MRI [5,11] . CEUS does not use ionizing radiation as does CT. CEUS is also less costly than CT or MRI [12] . The microbubble contrast agent for CEUS is safe in patients with severe renal impairment, unlike those used in CT or MRI [13,14] .…”
Section: Advantages and Limitations Of Ceusmentioning
confidence: 99%
“…(1) assessment of nodules ≥ 10 mm detected on surveillance ultrasound; (2) assessment of observations that are indeterminate on prior CT or MRI (i.e., LR-3, LR-4, or LR-M); (3) detection of arterial phase hyperenhancement when it is suspected that contrast mistiming is suspected as a cause of lack of arterial enhancement on prior CT or MRI; (4) detection of CEUS washout when CT or MRI washout is indeterminate but shows APHE; (5) further evaluation of biopsied observation with inconclusive histology; (6) guiding biopsy or percutaneous ablation of observations difficult to visualize with precontrast US; (7) guiding biopsy of heterogeneous observations; (8) monitor changes in enhancement pattern over time for selected CEUS LR-3 or CEUS LR-4 observations; and (9) differentiating tumor in vein ('tumor thrombus') from bland thrombus. With regards to the first indication listed above, studies and experience have shown that having CEUS available at the time of surveillance ultrasound reduces time to diagnosis, healthcare expenditures, and patient anxiety [12,40] .…”
Section: Indications For Ceusmentioning
confidence: 99%